MARITIME AUTONOMOUS VEHICLES: NEW FRONTIERS IN THE LAW OF THE SEA. Issue 3 (July 2020) - Klein, Natalie; Guilfoyle, Douglas; Karim, Md Saiful; McLaughlin, Rob
Abstract: The ongoing development of diverse maritime autonomous vehicles for varied ocean activities—ranging from scientific research, security surveillance, transportation of goods, military purposes and commission of crimes—is prompting greater consideration of how existing legal frameworks accommodate these vehicles. This article brings together the core legal issues, as well as current developments in relation to commercial shipping, the law of naval warfare, and maritime security. This article captures how these issues are now being addressed and what other legal questions will likely emerge as the newest technology impacts on one of the oldest bodies of international law.